Dawnside Wedge Current System Formed During Intense Geomagnetic Storms. Issue 11 (9th November 2018) - Ohtani, S.; Gjerloev, J. W.; Anderson, B. J.; Kataoka, R.; Troshichev, O.; Watari, S.
Abstract: We investigate the formation and development of a large‐scale current system in the dawn sector during intense geomagnetic storms. Four events are selected based on the historical ranking of the westward deflections of the morningside midlatitude magnetic field. For each event the polar distribution of equivalent currents indicates a significant intensification of the westward electrojet (WEJ), which initially takes place at postmidnight and then extends eastward covering the entire dawn sector. The longitudinal confinement of the enhanced WEJ suggests that it closes with downward and upward field‐aligned currents (FACs) at its eastern and western ends, respectively, and therefore, the entire system may be envisioned as a wedge current. It is noted, however, that the primary closure of FACs is meridional, and those upward and downward FACs are considered to be unbalanced parts of the R1 and R2 currents. In one event dipolarization was observed in the dawnside plasma sheet near the magnetic conjugate point of the enhanced WEJ, and in another event a major auroral expansion was observed in the entire dawn sector. It is therefore suggested that the formation of the wedge current system and the subsequent expansion toward dayside is an ionospheric projection of the tail current reduction extending toward the dawnside flank. This wedge current system is similar to the substorm wedge current system except that it is centered at dawn. The recurrent formation of this dawnside current wedge in intense storms suggests that this is another distinct constituent of the storm time current system. Key Points: During geomagnetic storms a wedge current system forms recurrently in the dawn sector as the westward auroral electrojet (WEJ) intensifies Whereas the associated upward FAC stays at postmidnight, the intensified WEJ extends eastward presumably along with the downward FAC The dawnside wedge current system is accompanied by a major auroral intensification and the reduction of the cross‐tail current